2022
DOI: 10.1186/s12967-022-03511-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of functional pathways and molecular signatures in neuroendocrine neoplasms by multi-omics analysis

Abstract: Background Neuroendocrine neoplasms (NENs) represent a heterogeneous class of rare tumors with increasing incidence. They are characterized by the ability to secrete peptide hormones and biogenic amines but other reliable biomarkers are lacking, making diagnosis and identification of the primary site very challenging. While in some NENs, such as the pancreatic ones, next generation sequencing technologies allowed the identification of new molecular hallmarks, our knowledge of the molecular prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 98 publications
(91 reference statements)
2
13
0
Order By: Relevance
“…Consequently, the presence of genetic variations that are vulnerable to potential individualized therapies are definitely relevant, especially for patients with high grade GI‐NENs. Melone et al showed ATM‐dependent signaling was the most significant pathways in NEN patients of thyroid, pancreas, intestine, and lung by multi‐omics analysis 41 . In our study, BRAC1/2 and ATM alterations of ATM‐dependent signaling were found in GI‐NENs also.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Consequently, the presence of genetic variations that are vulnerable to potential individualized therapies are definitely relevant, especially for patients with high grade GI‐NENs. Melone et al showed ATM‐dependent signaling was the most significant pathways in NEN patients of thyroid, pancreas, intestine, and lung by multi‐omics analysis 41 . In our study, BRAC1/2 and ATM alterations of ATM‐dependent signaling were found in GI‐NENs also.…”
Section: Discussionsupporting
confidence: 71%
“…Melone et al showed ATM-dependent signaling was the most significant pathways in NEN patients of thyroid, pancreas, intestine, and lung by multi-omics analysis. 41 In our study, BRAC1/2 and ATM alterations of ATM-dependent signaling were found in GI-NENs also.…”
Section: F I G U R Esupporting
confidence: 68%
“…Recently, the overexpression of 13 selected circulating miRNAs has been described in NENs and medullar, in comparison to healthy subjects. It was the first study in which a set of circulating miRNAs was identified that could represent a tumor signature for NEN diagnostics [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA–seq procedure was performed as described previously [ 21 , 22 ]. Briefly, before use, total RNAs concentration, from three biological replicates of DLD1-pEGFP and DLD1-pEGFP_hRIZ2 cells, was measured using RNA HS kit on a Qubit fluorimeter (Life Technologies, Monza, Italy) while its quality and integrity assessed with the Agilent 4200 TapeStation System (Agilent Technologies, Milan, Italy).…”
Section: Methodsmentioning
confidence: 99%